2002
DOI: 10.1038/sj.bjp.0704878
|View full text |Cite
|
Sign up to set email alerts
|

Metformin enhances insulin signalling in insulin‐dependent and ‐independent pathways in insulin resistant muscle cells

Abstract: 1 Metformin lowers blood glucose levels in type 2 diabetic patients. To evaluate the insulin sensitizing action of metformin on skeletal muscle cells, we have used C2C12 skeletal muscle cells di erentiated in chronic presence or absence of insulin. 2 Metformin was added during the last 24 h of di erentiation of the C2C12 myotubes. Insulinstimulated tyrosine phosphorylation of insulin receptor (IR) and insulin receptor substrate-1 (IRS-1) was determined. 3 Chronic insulin treatment resulted in 60 and 40% reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
84
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(97 citation statements)
references
References 43 publications
10
84
1
2
Order By: Relevance
“…Second, AMPK activation by t-RVT definitely potentiated the insulin-induced Akt activation ( Figure 4B), leading to improvement of insulin sensitivity. Quite similar to our results, a couple of recent studies demonstrated that -lipoic acid as well as metformin has been reported to improve insulin sensitivity by activating AMPK (Kumar and Dey, 2002;Lee et al, 2005). Despite many efforts, the mechanism by which AMPK increase insulin sensitivity remains almost unknown.…”
Section: Discussionsupporting
confidence: 90%
“…Second, AMPK activation by t-RVT definitely potentiated the insulin-induced Akt activation ( Figure 4B), leading to improvement of insulin sensitivity. Quite similar to our results, a couple of recent studies demonstrated that -lipoic acid as well as metformin has been reported to improve insulin sensitivity by activating AMPK (Kumar and Dey, 2002;Lee et al, 2005). Despite many efforts, the mechanism by which AMPK increase insulin sensitivity remains almost unknown.…”
Section: Discussionsupporting
confidence: 90%
“…2a). Inhibition of insulin-stimulated glucose uptake in skeletal muscle contributes to the development of insulin resistance [6,8]. Insulin signalling is initiated by the recruitment of intracellular molecules to the activated IR-β due to its tyrosine phosphorylation, which activates a number of cellular responses [6,8].…”
Section: Resultsmentioning
confidence: 99%
“…2b). IRS-1 is a key regulator, downstream from IR-β in the insulin-signalling cascade, and is phosphorylated on multiple tyrosine residues [6,8]. When L6E9 cells were pretreated with miltefosine, insulin-stimulated tyrosine phosphorylation of IRS-1 (1.92-fold) was inhibited down to the basal level (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations